Structure-cytotoxicity relationship profile of 13 synthetic cathinones in differentiated human SH-SY5Y neuronal cells - Soares, Jorge (2020)
Synthetic cathinones also known as β-keto amphetamines are a new group of recreational designer drugs. We aimed to evaluate the cytotoxic potential of thirteen cathinones lacking the methylenedioxy ring and establish a putative structure-toxicity profile using differentiated SH-SY5Y cells, as well as to compare their toxicity to that of amphetamine (AMPH) and methamphetamine (METH). Cytotoxicity assays [mitochondrial 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) reduction and lysosomal neutral red (NR) uptake] performed after a 24-h or a 48-h exposure revealed for all tested drugs a concentration-dependent toxicity. The rank order regarding the concentration that promoted 50 % of toxicity, at 24 h exposure, by the MTT assay was: 3,4-dimethylmethcathinone (3,4-DMMC)>METH > mephedrone ≈ α-pyrrolidinopentiophenone > AMPH ≈ methedrone > pentedrone > buphedrone ≈ flephedrone>α-pyrrolidinobutiophenone > methcathinone ≈ N-ethylcathinone>α-pyrrolidinopropiophenone>N,N-dimethylcathinone ≈ amfepramone. Apoptotic cell death signs were seen for all studied cathinones. 3,4-DMMC, methcathinone and pentedrone triggered autophagy activation, as well as increased reactive oxygen species production, and N-acetyl-L-cysteine (NAC) totally prevented that rise. Importantly, NAC was also able to prevent the cytotoxicity promoted by 6 tested drugs, ruling for an involvement of oxidative stress in the toxic events observed. The increased lipophilic chain on the alpha carbon, the presence and the high steric volume occupied by the substituents on the aromatic ring, and the substitution of the pyrrolidine ring by its secondary amine analogue have proved to be key points for the cytotoxicity profile of these cathinones. The structure-toxicity relationship established herein may enlighten future human relevant mechanistic studies, and future clinical approaches on intoxications.